Primary squamous cell carcinoma of the sigmoid colon: a case report and literature review - Pascacio Fiori, Martín (2021)
Primary squamous cell carcinoma of the colon is extremely rare. The etiology is poorly understood, and currently, there are different hypotheses about the origin of this malignant neoplasm. Here, we r 87-year-old male with a moderately-differentiated nonkeratinizing squamous cell carcinoma of the colon.